‘The knowledge question’ in the Norwegian curriculum - Sundby, Anniken Hotvedt; Karseth, Berit (Curriculum journal (London, England), 2022)
‘The knowledge question’, addressing what students need to know and learn, becomes particularly relevant during the process of a new school reform. This paper examines the political messages and the role of knowledge in the current curriculum reform initiative for primary and secondary education in Norway (2020). The study is based on a document analysis of four key policy documents and one subject curriculum. Analysis reveals that, although the messages in the policy documents express expectations of strengthening the knowledge dimension in the school subjects, analysis of a new subject curriculum framework indicates that it more clearly prescribes skills, methods and strategies than the specialised knowledge content to teach. We conclude that the continuation of a competency‐oriented curriculum model, wherein the competence aims are the governing category, explicit content is difficult to prescribe because of the contrasting assumptions that underline a content‐oriented versus a competence‐oriented curriculum. The two curriculum models demand different approaches to ‘the knowledge question’, and raises questions about whether combining these two orientations in one curriculum model is possible.